Location-Aware Cross-Layer Design Using Overlay Watermarks - Xianbin Wang; Paul Ho; Yiyan Wu (Advances in Multimedia)
A new orthogonal frequency division multiplexing (OFDM) system embedded with overlay watermarks for location-aware cross-layer design is proposed in this paper. One major advantage of the proposed system is the multiple functionalities the overlay watermark provides, which includes a cross-layer signaling interface, a transceiver identification for position-aware routing, as well as its basic role as a training sequence for channel estimation. Wireless terminals are typically battery powered and have limited wireless communication bandwidth. Therefore, efficient collaborative signal processing algorithms that consume less energy for computation and less bandwidth for communication are needed. Transceiver aware of its location can also improve the routing efficiency by selective flooding or selective forwarding data only in the desired direction, since in most cases the location of a wireless host is unknown. In the proposed OFDM system, location information of a mobile for efficient routing can be easily derived when a unique watermark is associated with each individual transceiver. In addition, cross-layer signaling and other interlayer interactive information can be exchanged with a new data pipe created by modulating the overlay watermarks. We also study the channel estimation and watermark removal techniques at the physical layer for the proposed overlay OFDM. Our channel estimator iteratively estimates the channel impulse response and the combined signal vector from the overlay OFDM signal. Cross-layer design that leads to low-power consumption and more efficient routing is investigated.